Numerical solution of tumor growth using Bertalanffy model / Farhah Qistina Harizam, Muhammad Assnali Akbar Mohd Taib and Nik Muhammad Fadhli Syah Nik Mohd Nor Azmi - Harizam, Farhah Qistina; Mohd Taib, Muhammad Assnali Akbar; Nik Mohd Nor Azmi, Nik Muhammad Fadhli Syah (2018)
Many mathematical models for tumor growth have been suggested in the past to enhance the understanding of tumor growth processes. This study evaluates the Bertalanffy model. The problems of Cancer in Malaysia have become increasingly important as it is the major killer disease. Thus, Bertalanffy model can be applied to calculate the rate of changes of tumor size in the following time. The purposes of this research is to obtain the exact solution of the Bertalanffy population model related to tumor growth and to use an appropriate numerical method to solve Bertalanffy population model and make comparison with the exact solution. We used Euler's method for numerical solution and solving the mathematical model by using Mathematical I software. It has given the best approximation towards an exact solution and give the best fitting curve in graphical approach.